2005
DOI: 10.1128/iai.73.11.7170-7179.2005
|View full text |Cite
|
Sign up to set email alerts
|

Distinct CD4+-T-Cell Responses to Live and Heat-InactivatedAspergillus fumigatusConidia

Abstract: Aspergillus fumigatus is an important fungal pathogen that causes invasive pulmonary disease in immunocompromised hosts. Respiratory exposure to A. fumigatus spores also causes allergic bronchopulmonary aspergillosis, a Th2 CD4؉ -T-cell-mediated disease that accompanies asthma. The microbial factors that influence the differentiation of A. fumigatus-specific CD4 ؉ T lymphocytes into Th1 versus Th2 cells remain incompletely defined. We therefore examined CD4؉ -T-cell responses of immunologically intact mice to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
74
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 55 publications
7
74
0
2
Order By: Relevance
“…Rivera et al informed that Th 1 type cytokines were formed predominantly during the exposure to live conidia while the production of Th2 type cytokine was prominent following the immunization with heat inactivated conidia [13]. We observed that Th2 response was more prominent following the infection with live conidia.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Rivera et al informed that Th 1 type cytokines were formed predominantly during the exposure to live conidia while the production of Th2 type cytokine was prominent following the immunization with heat inactivated conidia [13]. We observed that Th2 response was more prominent following the infection with live conidia.…”
Section: Discussionsupporting
confidence: 63%
“…Rivera et al also informed that humoral immune responses to A. fumigatus antigens mounted in mice infected with live but not heat-inactivated fungus [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding may play a role in mediating adaptive responses to the fungus as well. Recently, Rivera et al (29) found that mice exposed to live A. fumigatus conidia develop Th1-biased CD4 ϩ T cell responses, whereas mice exposed to inactivated conidia demonstrate CD4 ϩ T cell responses that are more Th2 biased. The data suggest that differential recognition of conidia and hyphae can skew downstream adaptive immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Cells producing IFN-γ are induced by Aspergillus in immunocompetent mice. Live conidia, which undergo swelling and germination, are able to prime Th1 responses [38] specific for C. albicans, Pneumocystis carinii, and Criptococcus spp. The observation that mice deficient in IL-17RA show an increased susceptibility to disseminated C. albicans infection first demonstrated the critical involvement of Th17 responses in protective anti-Candida host defenses [41].…”
mentioning
confidence: 99%